-33=2(v-6)-5v

Simple and best practice solution for -33=2(v-6)-5v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33=2(v-6)-5v equation:


Simplifying
-33 = 2(v + -6) + -5v

Reorder the terms:
-33 = 2(-6 + v) + -5v
-33 = (-6 * 2 + v * 2) + -5v
-33 = (-12 + 2v) + -5v

Combine like terms: 2v + -5v = -3v
-33 = -12 + -3v

Solving
-33 = -12 + -3v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '3v' to each side of the equation.
-33 + 3v = -12 + -3v + 3v

Combine like terms: -3v + 3v = 0
-33 + 3v = -12 + 0
-33 + 3v = -12

Add '33' to each side of the equation.
-33 + 33 + 3v = -12 + 33

Combine like terms: -33 + 33 = 0
0 + 3v = -12 + 33
3v = -12 + 33

Combine like terms: -12 + 33 = 21
3v = 21

Divide each side by '3'.
v = 7

Simplifying
v = 7

See similar equations:

| a+a.32=-325 | | (x+2)*(x+2)=14 | | -7x=6+3 | | 7/10=n/6 | | 3(m-2)=2(m+1)-3 | | 5/3u-1=-1/2u-1/2 | | 2=y+x+7 | | y/2-5=y/3-4 | | 30/6=10/n | | 7n+14=-21 | | 3x*x+4=16 | | y=3y^2-5 | | 77=8x | | 17x+1=19x-7 | | 3(4w)= | | 0-2=12-2*5-5 | | 4(2x-1)+3(x-5)=14 | | 7.6x-3.7=-62.4 | | 4w*3= | | 3x+3=9x+18 | | 4/10=2/x | | 2x+x=3800 | | 5n/28-6/7=13/4 | | x/3-12=27 | | 2(x-3)/3 | | X(5x-4)=(5x+1)(x-3) | | 4x+6-x-9=3(x+5) | | 2x+13x=17+3 | | (z*10)-7=1 | | Senx=-0.22 | | 2x+3x=17+3 | | -4(3x-5)=-5x-20-3x |

Equations solver categories